Modeling localized corrosion of pipeline steels in oilfield produced water environments. (September 2017) - Velázquez, J.C.; Cruz-Ramirez, J.C.; Valor, A.; Venegas, V.; Caleyo, F.; Hallen, J.M.
Abstract: A model for the estimation of the time evolution of maximum depth of localized corrosion defects caused under oilfield produced water environments has been developed. It takes into consideration the chemical composition of the produced water and other physical parameters. Immersion tests were conducted using coupons of an API 5L X60 pipeline steel under different experimental conditions and periods. The time dependence of the maximum pit depth was modeled as a power function of time, which was successfully fitted to the obtained experimental data using regression analysis. The main result of this analysis was represented by a holistic model which includes the most important variables involved in the pipeline internal corrosion process in produced waters. Highlights: A mathematical model to estimate the corrosion defect depth under produced water environments in carbon steel was performed This model takes into account the main chemical and physical characteristics of the oilfield produced waters It is possible to show the influence of each variable involved in the corrosion process under produced water environments The obtained model could help engineers in developing corrosion management programs